2014
DOI: 10.1063/1.4862496
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Fixed-node errors in quantum Monte Carlo: Interplay of electron density and node nonlinearities

Abstract: Perspective: Explicitly correlated electronic structure theory for complex systems

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 20 publications
(31 reference statements)
2
50
0
Order By: Relevance
“…However, unlike the present case, the magnitude of the fixed-node errors has to be addressed and it has been shown that large differences in the fixed-node errors can appear depending on the degree of node nonlinearity [91]. In the case of large fixed-node errors, the performance of the FCI-QMC method developed by Alavi and coworkers [92][93][94][95] will be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike the present case, the magnitude of the fixed-node errors has to be addressed and it has been shown that large differences in the fixed-node errors can appear depending on the degree of node nonlinearity [91]. In the case of large fixed-node errors, the performance of the FCI-QMC method developed by Alavi and coworkers [92][93][94][95] will be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of B i s is to qualitatively reflect the expected rise of FN bias with higher bond multiplicity 47 . In linear HCN dimer, for instance, we set B 1 = 3 and B 2 = 1 since the hydrogen bond (contact) consists of triply-bound nitrogen and hydrogen.…”
Section: Definitionsmentioning
confidence: 99%
“…We thus propose to use another measure, based on δ, reflecting also the fact that, in general, FN errors depend on electron density 47 . Although this requires a deeper study, as an example, we define here an empirical measure κ that progressively depends on a maximum bond multiplicity of terminal atoms constituing noncovalent contact/s (Eq.…”
Section: Small Noncovalent Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] Recently, Mitas and coworkers have discovered a interesting relationship between electronic density, degree of node nonlinearity and fixed-node error. [16][17][18] Here, we study the topology and properties of the nodes in a class of systems composed of electrons located on the surface of a sphere. Due to their high symmetry and their mathematical simplicity, these systems are the ideal "laboratory" to study nodal hypersurface topologies in electronic states.…”
Section: Introductionmentioning
confidence: 99%